The Effects of Magnetically Treated Water on the Performance and Immune System of Broiler Chickens - Al-Mufarrej, S.; Al-Batshan, H.A.; Shalaby, M.I.; Shafey, T.M. (International Journal of Poultry Science, 2005)
The effects of water treatment (tab water (CTW) vs. magnetically treated water (MTW)) on the performance (body weight gain, feed intake, feed conversion ratio (feed/gain)) from day to 32 days of age, water consumption (WC) and Water: feed consumption ratio (WFR) during the first three weeks of age (starter phase), carcass composition at 32 days of age, and antibody responses to SRBS antigens of sexed broiler chickens were investigated. MTW was prepared by exposing the water to a magnetic field of approximately 500 gauss. The exposure of water to the magnetic field slightly increased the pH of water from 7.72 to 7.86. The water treatment influenced WC of birds. The daily WC of birds on the MTW was significantly (P<0.05) lower than those on the CTW during the starter phase. The MTW did not influence the WFR during the starter phase, and performance and carcass composition of birds at 32 days of age. Sex of birds influenced body weight gain, and carcass composition at 32 days of age and WC over the starter phase. Males consumed more water, and had a heavier weight gain with high proportions of thigh and drumstick in their carcasses than females. Sex of birds did not influence feed intake and FCR at 32 days of age, and WFR at the starter phase. Water treatment and sex of bird did not influence antibody responses to SRBC antigens. There were significant interaction between water treatment and sex of birds on feed intake, weight gain, WC, and thigh proportion of the carcass. Males consumed more feed and water and had a higher weight gain than females when they drank the CTW, but not when they drank the MTW. Males had a higher thigh proportion in their carcasses than females when they drank the MTW, but not when they drank the CTW. It is concluded that the exposure of tab water to a magnetic field of approximately 500 gauss reduced water consumption, but did not significantly influence the performance, carcass composition and immune system of broiler chickens. Additionally, magnetically treated water reduced the difference in the performance between sexes of broiler chickens to a non-significant level.